2014
DOI: 10.1007/s10554-014-0532-7
|View full text |Cite
|
Sign up to set email alerts
|

Carotid magnetic resonance imaging for monitoring atherosclerotic plaque progression: a multicenter reproducibility study

Abstract: This study sought to determine the multicenter reproducibility of magnetic resonance imaging (MRI) and the compatibility of different scanner platforms in assessing carotid plaque morphology and composition. A standardized multi-contrast MRI protocol was implemented at 16 imaging sites (GE: 8; Philips: 8). Sixty-eight subjects (61 ± 8 years; 52 males) were dispersedly recruited and scanned twice within 2 weeks on the same magnet. Images were reviewed centrally using a streamlined semiautomatic approach. Quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 33 publications
(50 reference statements)
0
42
0
Order By: Relevance
“…All images were analyzed by trained readers who were blinded to clinical data. Plaque measurement reproducibility of MRI of the carotid artery analyzed by using Cascade has been reported previously (17)(18)(19). Each case was analyzed by two reviewers who arrived at a consensus opinion before recording the data.…”
Section: Image Analysismentioning
confidence: 99%
“…All images were analyzed by trained readers who were blinded to clinical data. Plaque measurement reproducibility of MRI of the carotid artery analyzed by using Cascade has been reported previously (17)(18)(19). Each case was analyzed by two reviewers who arrived at a consensus opinion before recording the data.…”
Section: Image Analysismentioning
confidence: 99%
“…However, these imaging techniques are applied mainly to determine the degree of luminal narrowing, which is an indispensable information, but a limited biomarker to determine the true impact on future cardiovascular events [3]. A more advanced imaging technique is multi-contrast CMR which became a well-recognized tool to study the complex composition of atherosclerotic plaques [4, 5]. The intrinsic soft tissue contrast and high spatial resolution makes CMR a well suited tool to delineate key constituents of plaque vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for the specification of disease, our results show an excellent interobserver agreement both on a per-patient level (Cohen's κ = 0.82) and on a per-vessel level (Cohen's κ = 0.83), which further demonstrates that the proposed imaging criteria can be used successfully by different readers. Recently, Sun et al reported a good to excellent interscan reproducibility of carotid MRI in patients with atherosclerotic disease, even in a multi-center setting with 3-T scanners of different vendors [13].…”
Section: Discussionmentioning
confidence: 99%